Closing yield gap is crucial to avoid potential surge in global carbon emissions. (July 2020) - Suh, Sangwon; Johnson, Justin A.; Tambjerg, Lau; Sim, Sarah; Broeckx-Smith, Summer; Reyes, Whitney; Chaplin-Kramer, Rebecca
Highlights: Rapidly growing maize demand may result in a large-scale agricultural expansion. Our model estimates ~ 4.0 Gt of additional CO2 emissions from the expansion. Expediting global yield improvement can reduce the emissions to ~ 1.1 Gt CO2 . Our results highlight the urgent need to close global yield gaps. Continued efforts to curb expansion in carbon-rich lands and forests are critical. Abstract: Global greenhouse gas (GHG) emissions models generally project a downward trend in CO2 emissions from land use change, assuming significant crop yield improvements. For some crops, however, significant yield gaps persist whilst demand continues to rise. Here we examine the land use change and GHG implications of meeting growing demand for maize. Integrating economic and biophysical models at an unprecedented spatial resolution, we show that CO2 emissions from land conversion may rise sharply if future yield growth follows historical trends. Our results show that ~4.0 Gt of additional CO2 would be emitted from ~23 Mha agricultural expansion from 2015 to 2026, under historical yield improvement trends. If yield gaps are closed expeditiously, however, GHG emissions can be reduced to ~1.1 Gt CO2 during the period. Our results highlight the urgent need to close global yield gaps to minimize agricultural expansion and for continued efforts to constrain agricultural expansion in carbon-rich lands and forests.